Submission 235: Parliament of Australia Select Committee on Nuclear Energy Inquiry into Nuclear Power Generation in Australia - Fullarton, Lex (Commonwealth of Australia, 2024)
This submission finds that ambient air temperature of the Australian continent has been rising steadily over the past 114 years. It finds that Australia has the highest per capita greenhouse gas emissions in the OECD and contributes 20 percent more GHGs that the entire population of the UK. A key method of reducing national GHG emissions is to find alternative methods to reduce emissions from fossil-fuelled based electricity generation.